Contribution of Food for Work Program to Food Security of Selected Workers in Kapasia Upazila under Gazipur of Bangladesh (The Agriculturists, 2015)
The main focus of the study was to determine the food security status of the women involved in food for work program in terms of access to food (meals/day/person) and intake of energy (kilo calorie) and to explore the relationship between some selected characteristics of the beneficiaries with the changes in food security. The study was conducted in Kapasia upazila of Gazipur district during July 2013 to September 2013. Data were collected through pre-tested interview schedule. One hundred and ten women were selected following simple random sampling method. All of the family members of the respondents used to take three-meals/day when Food for Work Program (FFW) program was ongoing. More than four-fifth (84.55%) of the household members received optimum to above optimum kcal/day when FFW was running, but only three-fifth (60.90%) of the respondents family members took optimum to above optimum kcal/day when FFW program did not run. Optimum level and above optimum level calorie in taking family members increased by 12.73 percent and 10.91 percent, respectively when FFW program was running. The difference between per capita calorie intake by the respondents and their family members when FFW program was and was not running was found significant. Correlation analyses showed that annual income and credit facility had positive and significant relationship with contribution of FFW program on changes in food security status of the beneficiaries. The Agriculturists 2014; 12(2) 83-90